Preparation of liposomal hydrogel containing Calendula and application as a wound dressing: liposomal hydrogel as a wound dressing - Naseriyeh, Tahereh; Kahrizi, Danial; Alvandi , Hosna; Rajati, Hajar; Behbood , Leila; Shahraky, Mahvash khodabandeh; Arkan, Elham (Cellular and Molecular Biology, 2022)
Burn wound is one of the major medical and Hydrogels are one of the best wound dressings for burns. Herein, chitosan/Aloe vera hydrogel was prepared and cross-linked by genipin. The nano-liposomes of soy lecithin as a phospholipid containing calendula were added to the hydrogel. The surface morphology and functional groups were evaluated by SEM and FTIR methods, respectively. The average hydrodynamic diameter was calculated by the dynamic light scattering. Also, the nanoliposomes hydrogel containing calendula has a suitable swelling and vapor permeability. The encapsulation rate of calendula was 83 % which indicates a high load of calendula. In vivo release study of hydrogel containing calendula was achieved by the French diffusion cell. Finally, the cytotoxicity (MTT) test, the proliferation and viability of fibroblast cells (L929) were investigated and the results show no cytotoxicity of the hydrogel. for in vitro study, the passage of calendula-containing liposomes through the skin was investigated. Rat abdominal skin was used as a natural membrane. France diffusion cell was used as a two-compartment model to measure the amount of passage. The skin absorption of the calendula begins with a gentle slope and in 24 h approximately 90% of skin absorption has taken place.